Algorithm of appointment (examination; consultation) of patients under follow-up care by a general practitioner - R. N. Shepel; P. V. Ipatov; L. Yu. Drozdova; А. M. Kalinina; M. M. Lukyanov; S. Yu. Martsevich; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2025)
A unified algorithm for appointment (examination; consultation) of patients under follow-up care by a general practitioner has been developed.In order to create the algorithm; we analyzed and systematized data on managing and conducting events within the appointment (examination; consultation) of outpatients by a general practitioner; contained in regulatory legal acts of the Russian Federation; clinical guidelines; scientific and methodological literature. Analytical and comparative methods; as well as the method of content analysis were used. The accumulation; adjustment; and systematization of the obtained results were carried out in Microsoft Office Excel 2016 spreadsheets.The algorithm for a dispensary appointment (examination; consultation) by a general practitioner consists of 9 following modules: patient intake; physical examination; assessing the achievement of health targets; assessing the risk of adverse events; assessing the results of consultations with specialists; establishing or clarifying the diagnosis of a disease (condition); prescribing preventive; diagnostic; therapeutic; and rehabilitation measures for medical reasons; informing the patient about the appointment (examination; consultation); preparing medical documentation.The developed algorithm contains systematized information on the activities within appointment (examination; consultation) of patients under follow-up care by a general practitioner; which will allow for the full implementation of prevention and timely detection of complications or exacerbations of diseases (conditions); treatment adjustment; reduction in the number of urgent hospitalizations; implementation of medical rehabilitation; therapeutic and preventive and health resort treatment.